2020
DOI: 10.18502/sjms.v15i5.7147
|View full text |Cite
|
Sign up to set email alerts
|

Ramadan 2020 and Beyond in the Midst of the COVID-19 Pandemic: Challenges and Scientific Evidence For Action

Abstract: Background: Ramadan is a sacred month in Islam, which involves 29–30 days of dawn-till-dusk dry-fasting. Millions of Muslims observed Ramadan fasting (RF) this year in the midst of the COVID-19 pandemic. Certain ethnic groups worldwide, including Muslims, have been disproportionately affected by COVID-19, raising fears that fasting could bring additional health risks. This directly impacted on the current challenges faced by health professionals. The COVID-19 virus is expected to become seasonal. Therefore, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 162 publications
(183 reference statements)
0
4
0
Order By: Relevance
“…76.3% of our participants answered correctly regarding this question. There had found disinterest in COVID-19 testing during the Ramadan period among many people as they assumed inserting a swab stick at nostrils might break their fast, as nasopharynx or oropharynx swab is taken as coronavirus sample [ 19 , 20 ]. In response to the questions, whether fasting would break or not due to testing for COVID-19, 80.1% give the exact answer that it will not break their fast.…”
Section: Discussionmentioning
confidence: 99%
“…76.3% of our participants answered correctly regarding this question. There had found disinterest in COVID-19 testing during the Ramadan period among many people as they assumed inserting a swab stick at nostrils might break their fast, as nasopharynx or oropharynx swab is taken as coronavirus sample [ 19 , 20 ]. In response to the questions, whether fasting would break or not due to testing for COVID-19, 80.1% give the exact answer that it will not break their fast.…”
Section: Discussionmentioning
confidence: 99%
“…The latter study reported a high prevalence of low physical activity among Saudi individuals with T2DM. Ramadan during the COVID-19 pandemic was very unusual for many people throughout the world, including those with type 2 diabetes and physical activity may have been further reduced due to lockdowns in some countries [51].…”
Section: Resultsmentioning
confidence: 99%
“…So that even though it is completed at home, our love has excellent quality. We are likewise asked not to return to our primary residences during this pandemic (Elmajnoun et al, 2020).…”
Section: Religious Expression During the Pandemic Disruptionmentioning
confidence: 99%